First Record of Miocene Polychaete Cirratulids in the Atlantic Ocean from the Pirabas Formation of Brazil: A MicroCT Approach - de Sousa da Silva, Jamille; Teixeira-Guimarães, Beatriz; Oliveira de Araújo, Olga; Kočí, Tomáš; Aguilera, Orangel; Tadeu Lopes, Ricardo (Anuário do Instituto de Geociências, 2025)
A new record of the cirratulid polychaete Diplochaetetes mexicanus Wilson, 1986 from the of Miocene Pirabas Formation outcrops (Burdigalian to Langhian) is documented in the context of the paleodiversity of the equatorial margin of Brazil and represents the first record for the equatorial shelf of South America. D. mexicanus, previously known from the Oligocene–Miocene interface of the Pacific in Mexico and from the Miocene of the Pacific in Peru, shows an amphi-American paleodistribution (Eastern Pacific and Western Atlantic) and a wide tropical to subtropical latitudinal range. The stratigraphic fidelity observed in the two studied outcrops (Praia do Atalaia and Fazenda on Fortaleza Island in north Brazil) is indicative of the species’ resilience under different paleoenvironmental conditions. MicroCT analyses and 3D reconstructions allowed for greater accuracy in the study of the colony.